HEALING COMPLEX DERMATITIS LESIONS WITH HERBAL CREAM PREPARATIONS - Junaedi, Putu Adrian; Suartha, I Nyoman; Sudimartini, Luh Made (Buletin Veteriner Udayana, 2020)
Dermatitis is a term of inflammation that occurs in the skin, resulting from infection with microorganisms and genetic factors, skin resistance and metabolism. The purpose of this study was to determine the healing of lesions in dogs that suffering from complex dermatitis that were given herbal cream preparations. The herbal cream used is derived from neem, pegagan and soursop plant extracts. This study used 4 dogs divided into 2 groups. Group A was 3 dogs that were given herbal cream preparations for 15 days and Group B was 1 dog as a control without herbal cream. Recovery of lesions was observed starting from day 0 to day 15. The data obtained were tested by the Wilcoxon test and analyzed descriptively. The results showed that in group A which was given herbal cream experienced a cure rate of lesions faster than group B without herbal cream. The administration of herbal cream had a significant effect (P<0.05) on dogs that suffering from complex dermatitis. Conclusion and the administration of herbal creams can accelerate healing of lesions in dogs that suffering from complex dermatitis.